2008
DOI: 10.1542/peds.2007-2558
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the HIV/AIDS Epidemic on the Neurodevelopment of Preschool-Aged Children in Kinshasa, Democratic Republic of the Congo

Abstract: OBJECTIVES-Pediatric HIV infection is a growing problem in most regions of the world. Data on the effects of HIV on the neurodevelopment of children in resource-poor settings are scarce but necessary to guide interventions. The purpose of this study was to compare the neurodevelopment of preschool-aged HIV-infected, HIV-affected (HIV-uninfected AIDS orphans and HIV-uninfected children whose mother had symptomatic AIDS), and healthy control children in Kinshasa, Democratic Republic of Congo. METHODS-Thirty-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
5
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 28 publications
6
134
5
2
Order By: Relevance
“…A possible confounding variable was that the authors were unable to determine the status of the apparently healthy comparison group, as well as being unable to control for other risk factors of early child development (see section 2.6). Van Rie et al (2008) found that 60% of HIV-infected children in the DRC showed severe cognitive delay, 28.6% showed severe motor delay, and 84.6% and 76.7% of HIV-infected children showed delay in language expression, and comprehension, respectively. Comparisons cannot be made between these studies as they both employed different assessments of child development.…”
Section: )?mentioning
confidence: 97%
See 4 more Smart Citations
“…A possible confounding variable was that the authors were unable to determine the status of the apparently healthy comparison group, as well as being unable to control for other risk factors of early child development (see section 2.6). Van Rie et al (2008) found that 60% of HIV-infected children in the DRC showed severe cognitive delay, 28.6% showed severe motor delay, and 84.6% and 76.7% of HIV-infected children showed delay in language expression, and comprehension, respectively. Comparisons cannot be made between these studies as they both employed different assessments of child development.…”
Section: )?mentioning
confidence: 97%
“…With increasing use of ART in paediatric populations in sub-Saharan Africa, researchers have identified the need to continue to research the effects of HIV on neurodevelopment in populations which are increasing in prevalence, for example preschoolers (Lowick, et al, 2012;Van Rie, et al, 2008). Lowick et al (2012) found that 90% of the HIV-infected children in Soweto, South Africa, exhibited general developmental delay despite ART.…”
Section: )?mentioning
confidence: 99%
See 3 more Smart Citations